If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 2(y + -8) = 4(y + 1) + -2 Reorder the terms: 7y + 2(-8 + y) = 4(y + 1) + -2 7y + (-8 * 2 + y * 2) = 4(y + 1) + -2 7y + (-16 + 2y) = 4(y + 1) + -2 Reorder the terms: -16 + 7y + 2y = 4(y + 1) + -2 Combine like terms: 7y + 2y = 9y -16 + 9y = 4(y + 1) + -2 Reorder the terms: -16 + 9y = 4(1 + y) + -2 -16 + 9y = (1 * 4 + y * 4) + -2 -16 + 9y = (4 + 4y) + -2 Reorder the terms: -16 + 9y = 4 + -2 + 4y Combine like terms: 4 + -2 = 2 -16 + 9y = 2 + 4y Solving -16 + 9y = 2 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -16 + 9y + -4y = 2 + 4y + -4y Combine like terms: 9y + -4y = 5y -16 + 5y = 2 + 4y + -4y Combine like terms: 4y + -4y = 0 -16 + 5y = 2 + 0 -16 + 5y = 2 Add '16' to each side of the equation. -16 + 16 + 5y = 2 + 16 Combine like terms: -16 + 16 = 0 0 + 5y = 2 + 16 5y = 2 + 16 Combine like terms: 2 + 16 = 18 5y = 18 Divide each side by '5'. y = 3.6 Simplifying y = 3.6
| 9z+17z=234 | | 0.09-0.01(x+2)=-0.03(3-x) | | 64m^3+27=0 | | -23=2a-10+1a | | 3t^2-15t=-18 | | 5r+15=155 | | 5(x+3)=2x-1 | | 4=0.22(4y-2) | | (2x+3)(7x^2+9x+6)= | | 6x+9=8-4x | | 2t-7=-3 | | 7r^2-252=0 | | -7.6x=60.8 | | .5x+3=3x-1 | | 8x+1=3(x+2) | | 9.1-1.3n=12 | | 3n+46=1 | | 12y^2-41y+35=0 | | 5(2x-3)=2(5x-4) | | 9x+6=10x-7 | | 1760=.80x | | 20W^2-25w^3= | | 4a+9=7a | | (5)-3a-4/5=7-2a/2 | | 9y+1-y=49 | | 1760=.20x | | 23x+5= | | 7+2z-6=7z+7-4z | | -3(x-8)=29 | | 4(k-3)=3(3k+6) | | 7x+5=3x-3 | | 3k+4=22 |